Distribution of Streptococcal Groups in Clinical Specimens with Evaluation of Bacitracin Screening - Pollock, Helen M. (1974)
During a 2-year period, 4,968 strains of beta-hemolytic streptococci were examined for the clinical source distribution and bacitracin sensitivity of each group. In the upper respiratory tract, groups A (51.7%) and C (20.4%) accounted for most of the isolates, and in wounds and exudates group A (79.1%) made up most of the isolates. Group B (71.2%) was the major component of isolates from the genitorinary tract and, while composing 29.3% of the lower respiratory tract isolates, competed with group A (18.8%) and the nongroupables (22.8%) for supremacy. Bacitracin screening showed that 0.5% of group A streptococci were resistant, and sensitive non-group A isolates were group B (2.6%), group C (6.0%), group G (8.0%), and the nongroupables (2.2%). It was found that those groups which were most predominant in wounds and the upper respiratory tract gave the highest rate of false positives with bacitracin, whereas the predominant group of the genitourinary tract gave the lowest rate of false positives.